5-6 GHz Front End Low Noise Amplifier - Othman, Abdul Rani; M. H. Che Halim; Abd Aziz, Mohamad Zoinol Abidin; Sahingan @ Samingan, Md Saiful Azri; M. F. Selamat; A. A. Abd Aziz (2008)
This paper presents 5-6 GHz front end Low Noise Amplifier application for IEEE standard 802.11 system for WLAN application. This amplifier uses FHX76LP Low noise SuperHEMT device designed for DBS application from Eudyna Device USA Inc.This paper is present design and simulation of single stage LNA circuits. A single stage LNA has successfully designed with 26.92 dB forward gain and 1.32 dB noise figure, which stable along the UNII frequency band.